(untitled) (Global Journal of Management and Business Research, 2011)
Sustainable development issues belong to external non-economical common land based concerns. From an historical viewpoint, the main responsibility for the current series of global environment problem should be taken on by developed countries. Therefore, on sustainable development issue, international society has formed a principle of "common but different" responsibility-sharing rule. By game theory model, it is found that the reason why the negotiation between developed countries and developing ones reaches a deadlock again and again is short of proper conditions or mechanism to co-operate. There are at least three prerequisites to solve sustainable development issues, none of which has been met so far.